2010
DOI: 10.1177/1538574410377019
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acarbose Treatment on Intimal Hyperplasia in a Rat Carotid Endarterectomy Model of Diet-Induced Insulin Resistance

Abstract: Glucose control by acarbose in rat carotid endarterectomy model of diet-induced insulin resistance resulted in attenuation of intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[2] Upregulated ROS production is implicated in atherosclerosis and restenosis. [2, 3133] Our studies suggest that HFHSD accelerates atherosclerotic lesions and increases intimal hyperplasia,[1518] which might be in part via increased ROS production, irreversible SERCA oxidation, and induced inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[2] Upregulated ROS production is implicated in atherosclerosis and restenosis. [2, 3133] Our studies suggest that HFHSD accelerates atherosclerotic lesions and increases intimal hyperplasia,[1518] which might be in part via increased ROS production, irreversible SERCA oxidation, and induced inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…[14], accelerates atherosclerotic lesions in minipigs and in LDL receptor deficient mice,[1517] and increases intimal hyperplasia after rat carotid endarterectomy. [18] Compared to another commonly used obesity model induced by high fat diet without sucrose,[19, 20] HFHSD fed mice gain less weight and have less insulin resistance. [21] These two obese models both develop glucose intolerance, insulin resistance, cardiac hypertrophy and myocardial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with metformin significantly improved these metabolic abnormalities. The observed effects of metformin are supported by the evidence that metformin decreases hepatic production of glucose and increases hepatic insulin sensitivity and glucose clearance [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…In many studies metformin has reduced both total cholesterol and LDL cholesterol levels [8486] , tri glyceride levels [84] and increased HDL levels [87,88] . Animal studies have shown that acarbose given to insulin resistant rats decreased carotid intimal hyperplasia and blood flow velocities [89] . Taken as a whole, the ability of metformin (and likely other insulin sensitizing agents) to elicit an over all reduction in the risk for CAD may be easier than the ability to produce consistent measureable improvements.…”
Section: Treatmentmentioning
confidence: 99%